Analysis of the Role and Performance of Business Incubator al-Ahmadi Entrepreneurship Center Batam Riau Island - Muthi'ah Khairiyah; Atiyah Fitri; Abdi Triyanto (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
This study aims to determine the performance of the Al Ahmadi Entrepreneurship business incubator in assisting the fostered businesses. Knowing the benefits of the incubation program on the performance of the fostered business. The method used in this research is descriptive quantitative. The data used in this study are primary and secondary data. The primary data was obtained from questionnaires distributed to the fostered business incubators, while the secondary data came from literature studies sourced from books, journals, reports or previous research. The data obtained were analyzed using the Balanced Scorecard (BSC) method. The results showed that the achievement score of Al-Ahmadi Entrepreneurship Center's performance was 82,127. According to Price Waterhouse Coopers Al- Ahmadi Entrepreneurship Center in mentoring fostered businesses is satisfactory. Al-Ahmadi Entrepreneurship Center has played a role in improving the performance of the fostered businesses seen from four indicators, namely increasing turnover, increasing the number of workers, increasing production capacity, and increasing access to sources of capital.